Appraising the evidence and applying it to make wiser decisions - Paolo Prolo; David J. Weiss; Ward Edwards; Francesco Chiappelli (Universidade Estadual de Campinas, 2015)
Over the past several decades, evidence based health care, and evidence based dentistry in particular, has come to be seen as the proper foundation for selecting a treatment program. Evidence based dentistry can be defined as the process of systematically evaluating the research evidence to determine the best treatment in everyday clinical practice. Integration of research evidence into practice relies on the ability of dentists to identify appropriately designed and conducted research, whose results have been correctly analyzed. However, questions arise as to the relevance of the published research to individual clinical needs, particularly in situations when either the published evidence is mixed or it cannot be translated into the present needs of the clinician. An algorithm is needed that is designed to aid the clinician in selectively reviewing the evidence and determining its applicability.